2015
DOI: 10.4137/dti.s24946
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants: A Potential Source of Compounds for Targeting Cell Division

Abstract: Modern medicinal plant drug discovery has provided pharmacologically active compounds targeted against a multitude of conditions and diseases, such as infection, inflammation, and cancer. To date, natural products from medicinal plants remain a solid niche as a source from which cancer therapies can be derived. Among other properties, one favorable characteristic of an anticancer drug is its ability to block the uncontrollable process of cell division, as cancer cells are notorious for their abnormal cell divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…A large number of authors have suggested the use of medicinal plants as antimutagenic agents in the prevention of genotoxic effects of different chemotherapeutic agents [22][23][24]. However, as far as we know, determination of the protective effects of T. polium and R. crispus extracts combined with any known mutagenic substance is not studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of authors have suggested the use of medicinal plants as antimutagenic agents in the prevention of genotoxic effects of different chemotherapeutic agents [22][23][24]. However, as far as we know, determination of the protective effects of T. polium and R. crispus extracts combined with any known mutagenic substance is not studied.…”
Section: Discussionmentioning
confidence: 99%
“…By these results, the previously declared clastogenic and genotoxic effect of CP has been confirmed Chemotherapeutic agents such as CP are toxic and many are mutagenic. Cyclophosphamide-mediated genotoxicity either occur induction of microtubule damages or DNA reactive intermediates or endogenous mutagenic agents [23,25]. Genotoxic substances induce damage in cells through interaction with the DNA and can result, including single-and double-strand breaks, cross-links between DNA bases and proteins, and chemical additions to the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…While antiproliferative compounds exert their anticancer effects through the inhibition of cell proliferation (Zulkipli et al. 2015 ), compounds with antitumorigenic activities may have a myriad of effects, which may prevent the development, maturation or spread of cancerous cells. Only one study has shown the potential antitumorigenic activity of CN.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Alternative lines of investigation for future studies could include investigating whether the antiproliferative effects of CN involve a cell division blockade or initiation of a cell death pathway (Zulkipli et al. 2015 ). Interestingly, in a recent study, high levels of the pro-apoptotic mediator, Bax, and apoptotic executioner protein, caspase 3, were detected by western blotting in tumor tissue from HepA tumor-bearing mice treated with a CN extract (Huang et al.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, 40%‐60% of CRC surgical treatment cases have high recurrence rates in the first 3 years after surgery, whereas chemotherapy and radiation therapy have severe side effects on patients, and CRC patients frequently resist chemotherapeutic drugs . Therefore, researchers are attempting to develop novel anticancer agents derived from natural sources to treat CRC, which may represent new attractive therapeutic options due to their lower toxicity on normal cells and tissues …”
Section: Introductionmentioning
confidence: 99%